Kiertotalousalueen liiketoimintamallin laatiminen: case Napapiirin kiertotalouspuisto - Liisanantti, Hanna (2023)
The purpose of the thesis is to research what kind of circular economy areas there are in Finland and what kind of circular economy businesses there are in the areas and how the areas have developed. The purpose is to create a business model to the circular economy area in the Arctic Circle. There is no model or guide on how to develop a circular economy area. Therefore, the different kinds of circular economy areas and circular economy business models are researched in the thesis. There are many kinds of circular economy areas. In the thesis the circular economy areas are classified into three different main groups that are eco-industrial parks, circular economy concepts or hubs, which are coordinated by municipal waste management companies, and circular economy platforms which support development of circular economy in the hub. There are many kinds of business models in the business world as well as in the circular economy branch. Open interviews, observation and benchmarking are used as methods to achieve results of different kinds of circular economy areas. The collected data is the ground to create new circular economy business models suitable for the Arctic Circle circular economy park. Developing of innovations is the research method. In the thesis a vision is created of what kind of circular economy business there can be in the Arctic Circle circular economy park. The main goal in the circular economy is to reduce waste. The waste is generated in every anthropological process. The waste can be reduced by different kinds of circular economy business models. Circular economy business models usually are product-life extension, product as a service, sharing platforms, recycling and resource efficiency and renewability. In this thesis the solution is that product-life extension, product as a service and sharing platform are business models that could be used in the Arctic Circle circular economy park. Päätavoite kiertotaloudessa on jätteen määrän vähentäminen. Jätettä syntyy kaikessa antropologisessa ...